Influence of Halal Label, Brand Image, and Product Quality on Purchase Decisions for Ms Glow Cosmetic Products - Vinna Nur Khasanah; Syuhada Syuhada (AJER: Advanced Journal of Education and Religion, 2024)
This study discusses how the influence of halal labeling, brand image, and product quality on purchasing decisions for Ms Glow cosmetic products. So that the purpose of this study is to determine whether there is an influence of halal labeling, brand image, and product quality on purchasing decisions for Ms Glow cosmetic products by the community in Karangkembang Village, Babat District. This study uses quantitative research methods, with data collection methods using questionnaires. In determining the research sample using the Slovin formula with a non-probality sampling technique so that the sample decision amounted to 80 people. The analysis method used in this research is multiple linear regression as follows Y = 3.316 + 0.271 X1 + 0.301 X2 + 0.160 X3. Based on statistical data analysis, the indicators in this study are valid and reliable. In classical assumption testing, the regression model is normal, free of multicollinearity, no heteroscedaticity. Based on the coefficient of determination test, it can be seen that R2 is 0.770, meaning that the halal label, brand image, and product quality influence purchasing decisions by 77%, while the rest is influenced by other factors outside the variables of this study. from the results of the T test in the study shows that the halal label affects purchasing decisions, brand image affects purchasing decisions, and product quality affects purchasing decisions. Meanwhile, the results of this study from the F test show that the three variables have a simultaneous or joint effect on purchasing decisions.